FLEXIBLE ELECTRODE MATERIAL AND MANUFACTURING THEREOF

JP7610882B2Active Publication Date: 2025-01-09INDUSTRYACADEMIC COOPERATION FOUNDATION GYEONGSANG NATIONAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023533887
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-17
Filing Date
2021-11-19
Publication Date
2025-01-09
Estimated Expiration
2041-11-19

AI Technical Summary

Benefits of technology

【0026】 本発明によるフレキシブル電極素材は、グラフェンフィルム上にフリースタンディング金属酸化物を直接形成させることによって、エネルギー貯蔵性能、容量維持率、サイクリング安定性が向上した効果があり、柔軟性及び防水性に優れた効果がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610882000004
    Figure 0007610882000004
  • Figure 0007610882000005
    Figure 0007610882000005
  • Figure 0007610882000006
    Figure 0007610882000006
Patent Text Reader

Abstract

The present invention relates to a flexible electrode material and a manufacturing method thereof. One aspect of the present invention provides a flexible electrode material including a graphene film and a free-standing metal oxide formed on the graphene film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flexible electrode material and a method for producing the same. [Background technology]

[0002] Zinc-ion batteries are composed of a zinc anode, an oxide cathode, an electrolyte, and a separator. They have excellent stability, environmental friendliness, and high specific capacity, and are attracting attention as a next-generation flexible, portable energy storage device.

[0003] In particular, zinc is the core electrode material of zinc-ion batteries, and is a very safe material that is inexpensive and environmentally friendly. It is not only relatively stable compared to lithium, sodium, and potassium, but also has a high theoretical capacity and excellent compatibility with electrolytes, which allows the battery to achieve high energy density and long life.

[0004] The energy storage mechanism of a zinc-ion battery is the insertion and removal of zinc ions from the cathode to the zinc electrode during charging, and the insertion and removal of zinc ions from the cathode during discharging.

[0005] At this time, the degree of zinc ion storage in the cathode is the most important factor in determining the energy storage performance of a zinc ion battery, so it is very important to select an appropriate cathode material.

[0006] In this regard, vanadium-based electrode materials such as VS2, V2O5, and VO2, which have high specific capacity and excellent long-term stability, have been researched, but they have problems that make their application difficult due to their high cost and toxicity.

[0007] In contrast, manganese oxide has the advantages of low cost, excellent theoretical capacity, and high operating voltage, making it suitable as an electrode material for zinc-ion batteries. However, the use of a binder and metal current collector causes a rapid decrease in capacity and shows low cycling stability.

[0008] Therefore, it is necessary to develop an electrode material that can improve the capacity retention rate, cycling stability, etc. while ensuring the excellent energy storage performance of zinc-ion batteries.

[0009] The above-mentioned background art is owned or acquired by the inventors in the process of arriving at the contents of the disclosure of this application, and is not necessarily publicly known art that was disclosed to the general public prior to the filing of this application. Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention is intended to solve the above-mentioned problems, and an object of the present invention is to provide a flexible electrode material and a manufacturing method thereof that can improve the energy storage performance, capacity retention rate and cycling stability of a zinc ion battery.

[0011] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by a person of ordinary skill in the art from the following description. [Means for solving the problem]

[0012] One aspect of the present invention provides a flexible electrode material, comprising: a graphene film; and a free-standing metal oxide formed on the graphene film.

[0013] According to one embodiment, the graphene film may comprise graphene or a plurality of graphene stacks.

[0014] According to one embodiment, the graphene film may be surface-activated to have oxygen (O)-containing functional groups on the surface.

[0015] According to one embodiment, the metal oxide may comprise one or more selected from the group consisting of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, V2O5, and V2O5·nH2O.

[0016] The content of the metal oxide may be 1% to 10% by weight.

[0017] According to one embodiment, the length of the metal oxide in a direction perpendicular to the surface of the graphene film may be 10 nm to 200 nm.

[0018] According to one embodiment, the metal oxide may be directly bonded to the surface of the graphene film.

[0019] According to one embodiment, the flexible electrode material may be binder-free.

[0020] According to one embodiment, the electrode may be for a zinc ion battery.

[0021] Another aspect of the present invention provides a method for manufacturing a flexible electrode material, the method including: preparing a mixed solution by dissolving graphene and polyvinylidene fluoride (PVDF) in a solvent; casting the mixed solution into a mesh and heating it to form a graphene film; separating the graphene film from the mesh; and floating the graphene film in a metal oxide precursor solution and then stirring the metal oxide precursor solution.

[0022] According to one embodiment, the mixed solution is cast into a mesh by a doctor blade method, and the heating may be performed at a temperature of 50°C to 150°C.

[0023] According to one embodiment, the method may further include the steps of separating the graphene film from a mesh and then surface activating the separated graphene film.

[0024] According to one embodiment, the metal oxide is manganese oxide, and the metal oxide precursor solution may include potassium permanganate (KMnO4), sulfuric acid (H2SO4), and deionized water (DIW).

[0025] According to one embodiment, the stirring may be carried out for 30 minutes to 90 minutes. Effect of the Invention

[0026] The flexible electrode material according to the present invention has the effects of improving energy storage performance, capacity retention rate, and cycling stability by directly forming a freestanding metal oxide on a graphene film, and has the effects of excellent flexibility and waterproofness.

[0027] In addition, the method for manufacturing a flexible electrode material according to the present invention can selectively grow a metal oxide on a graphene film without a binder or additive, thereby solving problems such as a decrease in battery capacity and low cycling stability caused by a binder, and has an advantage that an electrode material having excellent flexibility and electrochemical performance can be manufactured in a relatively simple manner.

[0028] Furthermore, the zinc ion battery including the flexible electrode material according to the present invention can have excellent electrochemical performance, stability, flexibility and waterproofness, which is advantageous in both aqueous zinc ion batteries and all-solid-state zinc ion batteries. [Brief description of the drawings]

[0029] [Figure 1] 1A to 1C are diagrams illustrating a manufacturing process of a flexible electrode material according to an embodiment of the present invention. [Diagram 2] 1A and 1B are diagrams illustrating the structural form of an electrode material according to one embodiment of the present invention. [Figure 3A] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to an embodiment of the present invention, and is a photograph showing a surface-activated graphene film in a bent state. [Figure 3B] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention; FIG. 2 is an FE-SEM image of a surface-activated graphene film. [Figure 3C] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 1. [Figure 3D] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 2. [Figure 3E] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 3. [Figure 3F] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention; FIG. 2 is an FE-SEM image of a surface-activated graphene film. [Figure 3G] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 1. [Figure 3H] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 2. [Figure 3I] 1 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention, and is an FE-SEM image of the flexible electrode material of Example 3. [Figure 4A] 1 is a cross-sectional FE-SEM image (scale bar 500 nm) of a flexible electrode material of Example 2 according to an embodiment of the present invention. [Figure 4B] 4B is a cross-sectional FE-SEM image (scale bar 50 nm) of a flexible electrode material of Example 2 according to an embodiment of the present invention, which is an enlarged view of the area indicated by the square in FIG. 4A. [Figure 5A]1 is a low-resolution HR-TEM image of a flexible electrode material of Example 2 according to an embodiment of the present invention. [Figure 5B] FIG. 5B is a high-resolution HR-TEM image of the flexible electrode material of Example 2 according to one embodiment of the present invention, which is an enlarged view of the area indicated by the square in FIG. 5A. [Figure 5C] 1 is an EDS mapping image of a flexible electrode material of Example 2 according to an embodiment of the present invention. [Figure 6A] 1 is a TGA result of a flexible electrode material according to an embodiment of the present invention. [Figure 6B] 1 is an XRD result of a flexible electrode material according to an embodiment of the present invention. [Figure 6C] 1 is an XPS result of a flexible electrode material according to an embodiment of the present invention. [Figure 6D] 1 is an XPS result of a flexible electrode material according to an embodiment of the present invention. [Figure 7A] FIG. 1 shows the results of analyzing electrochemical characteristics of coin cells manufactured using the electrode materials of the Comparative Example and Examples 1 to 3, in which commercial MnO2 powder, PVDF binder, and conductive carbon black (Ketjen black) are cast onto a surface-activated graphene film, and Nyquist plots of the cells manufactured using the electrode materials of the Comparative Example and Examples 1 to 3. [Figure 7B] FIG. 13 is a result of analyzing electrochemical characteristics of coin cells manufactured using electrode materials of a comparative example and examples 1 to 3 in which commercial MnO2 powder, PVDF binder, and conductive carbon black (Ketjen black) are cast on a surface-activated graphene film, and is a graph showing the relationship between Zreal and ω-1 / 2 in cells manufactured using the electrode materials of a comparative example and examples 1 to 3. [Figure 7C]FIG. 13 is a result of analyzing electrochemical characteristics of coin cells manufactured using the electrode materials of the Comparative Example and Examples 1 to 3 in which commercialized MnO2 powder, PVDF binder, and conductive carbon black (Ketjen black) are cast on a surface-activated graphene film, and is a graph showing the Zn ion diffusion coefficient of cells manufactured using the electrode materials of the Comparative Example and Examples 1 to 3. [Figure 8A] FIG. 1 is a graph showing the electrochemical performance of cells manufactured using the electrode materials of Comparative Example and Examples 1 to 3, and shows the rate performance at potentials in the range of 1.0 to 1.9 V and current densities in the range of 0.1 to 2.0 Ag-1 of the cells manufactured using the electrode materials of Comparative Example and Examples 1 to 3. [Figure 8B] FIG. 1 is a graph showing the electrochemical performance of cells manufactured using the electrode materials of the comparative example and examples 1 to 3, and a graph showing the capacity change over 300 cycles at a current density of 1.0 Ag-1 for cells manufactured using the electrode materials of the comparative example and examples 1 to 3. [Figure 9] The energy and power densities of cells fabricated with the electrode material of Example 2 are compared by Ragone plots to other reported energy storage devices using electrolyte solutions. [Figure 10] FIG. 1 shows a schematic diagram of an all-solid-state zinc-ion battery structure using flexible electrode material and gel electrolyte according to one embodiment of the present invention. [Figure 11A] This shows the life performance and cycling stability of an all-solid-state zinc ion battery using a flexible electrode material and a gel electrolyte according to one embodiment of the present invention, and shows the rate characteristics at a potential in the range of 1.0 to 1.9 V and a current density in the range of 0.3 to 1.0 Ag-1 of the all-solid-state zinc ion battery according to one embodiment of the present invention. [Figure 11B]FIG. 1 shows the life performance and cycling stability of an all-solid-state zinc-ion battery using a flexible electrode material and gel electrolyte according to an embodiment of the present invention; and FIG. 2 is a Ragone plot comparing the energy and power density of an all-solid-state zinc-ion battery according to an embodiment of the present invention with previously reported all-solid-state energy storage devices. [Figure 11C] FIG. 1 shows the life performance and cycling stability of an all-solid-state zinc-ion battery using a flexible electrode material and gel electrolyte according to an embodiment of the present invention, and shows the cycling stability at a current density of 0.5 Ag-1 in flat and folded states and in the presence and absence of water of the all-solid-state zinc-ion battery according to an embodiment of the present invention. [Figure 12] 5 is a photograph showing an experiment to confirm the operation of an all-solid-state zinc ion battery according to an embodiment of the present invention in water and in a bent state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the embodiments will be described in detail with reference to the accompanying drawings. However, since various modifications can be made to the embodiments, the scope of the patent application is not restricted or limited by these embodiments. All modifications, equivalents or alternatives to the embodiments should be understood to be within the scope of the claims.

[0031] The terms used in the examples are used for descriptive purposes only and should not be construed as limiting. A singular expression includes a plural expression unless the context clearly indicates otherwise. As used herein, terms such as "comprise" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described herein, but are to be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0032] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by one of ordinary skill in the art to which the embodiments belong. Terms defined in commonly used dictionaries should be interpreted to have a meaning consistent with the contextual meaning of the relevant art, and are not to be interpreted as idealized or overly formal unless expressly defined in this application.

[0033] In addition, when describing the present invention with reference to the accompanying drawings, the same components are given the same reference numerals regardless of the drawing numerals, and redundant description thereof will be omitted. In describing the embodiments, if it is determined that a detailed description of related publicly known techniques may unnecessarily obscure the gist of the embodiments, the detailed description will be omitted.

[0034] Additionally, terms such as first, second, A, B, (a), (b), etc. may be used to describe components of an embodiment. These terms are used to distinguish a component from other components, and do not limit the essence, order, or sequence of the corresponding components. When a component is described as being "coupled," "coupled," or "connected" to another component, it should be understood that the components may be directly coupled or connected to the other components, but that there may also be other components "coupled," "coupled," or "connected" between each component.

[0035] Components included in any one embodiment and components including common functions will be described using the same names in other embodiments. Unless otherwise specified, the description of any embodiment may be applied to other embodiments, and detailed description will be omitted to the extent that they overlap.

[0036] One aspect of the present invention provides a flexible electrode material that includes a graphene film and a free-standing metal oxide formed on the graphene film.

[0037] The flexible electrode material according to the present invention is characterized by having flexibility as well as improved electrochemical performance due to the metal oxide being bound to the surface of the graphene film without a binder.

[0038] The flexible electrode material according to the present invention does not include a binder, thereby improving charge mobility, and the free-standing metal oxide is uniformly formed on the graphene film, thereby improving zinc ion diffusion ability.

[0039] FIG. 1 is a diagram illustrating a manufacturing process of a flexible electrode material according to an embodiment of the present invention.

[0040] Referring to FIG. 1, a flexible electrode material can be obtained by selectively growing manganese dioxide (MnO2), a metal oxide, on a graphene film.

[0041] FIG. 2 is a diagram showing a structural configuration of a flexible electrode material according to one embodiment of the present invention.

[0042] Referring to FIG. 2, in a flexible electrode material according to an embodiment of the present invention, a flexible graphene film serves as a current collector and a platform on which a metal oxide can be uniformly grown on the surface, and the metal oxide (MnO2) grown in a needle shape on the graphene film improves the diffusion ability and charge transfer properties of zinc ions, thereby improving the specific capacity and cycling stability of a battery at a high current density.

[0043] In particular, the flexible electrode material according to the present invention has an effect that it can be applied to all-solid-state batteries that use gel electrolytes.

[0044] The free-standing metal oxide is a metal oxide that stands in a direction perpendicular to the surface of the graphene film, and may be independently bound without a separate binder or support.

[0045] The freestanding metal oxide is attached to the surface of the graphene film without a separate binder or additive, thereby suppressing the rapid capacity loss and cycling stability loss of the battery caused by the use of a binder or additive.

[0046] That is, side reactions and active material decomposition caused by the use of binders or additives can be prevented, and ion diffusion ability and charge mobility can be improved, thereby improving the performance of the battery.

[0047] According to one embodiment, the free-standing metal oxide may be needle-like and may be formed perpendicular to the surface of the graphene film.

[0048] The free-standing metal oxide can be uniformly distributed on the graphene film. The uniform distribution of the free-standing metal oxide particles can improve the diffusion capacity of zinc ions.

[0049] According to one embodiment, the graphene film may comprise graphene or a plurality of graphene stacks.

[0050] The graphene film may include a single graphene or may be in the form of a stack of multiple graphenes.

[0051] The graphene film may have a layered structure including a plurality of stacked graphenes, thereby ensuring flexibility.

[0052] The graphene film can act as a current collector and has the advantage of excellent chemical resistance.

[0053] Additionally, it can improve the electrical conductivity of metal oxides to provide superior electrochemical performance and aid in the growth of the free-standing metal oxides.

[0054] According to one embodiment, the graphene film may be surface-activated to have oxygen (O)-containing functional groups on the surface.

[0055] In general, the poor wettability of graphene acts as a factor that prevents ions of the solution during aqueous synthesis from coming into contact with the carbon.

[0056] Therefore, by generating oxygen-containing functional groups on the surface of the graphene film through surface activation, i.e., surface functionalization, and increasing the wettability of the graphene film, it becomes possible to effectively synthesize metal oxides on the surface of the graphene film.

[0057] According to one embodiment, the surface activation may be an acid treatment or an etching step using an acid.

[0058] The acid treatment or etching step using acid may use an aqueous acid solution.

[0059] The surface activation forms oxygen-containing functional groups on the surface of the graphene film and generates surface defects, allowing metal oxides to be effectively synthesized on the surface of the graphene film.

[0060] According to one embodiment, the graphene film may be impurity-free.

[0061] According to one embodiment, the metal oxide may comprise one or more selected from the group consisting of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, V2O5, and V2O5·nH2O.

[0062] The manganese oxide has the advantages of being inexpensive, conforming to the theoretical capacity, and realizing a high operating voltage.

[0063] According to one embodiment, the metal oxide may be α-MnO2.

[0064] The α-MnO2 can accommodate a relatively large number of zinc ions, thereby achieving the effect of increasing the specific capacity of the electrode.

[0065] According to one embodiment, the content of the metal oxide may be 1% to 10% by weight.

[0066] If the content of the metal oxide is less than the above range, the effect of the active material cannot be exhibited, whereas if the content exceeds the above range, the ion diffusion ability and charge mobility may be decreased, resulting in a decrease in electrochemical performance.

[0067] According to one embodiment, the length of the metal oxide in a direction perpendicular to the surface of the graphene film may be 10 nm to 200 nm.

[0068] Preferably, the length of the metal oxide in a direction perpendicular to the surface of the graphene film may be 50 nm to 150 nm, more preferably 80 nm to 130 nm, and further preferably 100 nm to 120 nm.

[0069] If the length of the metal oxide in the direction perpendicular to the surface of the graphene film is less than the above range, the electrochemical performance may be degraded due to an increase in vacant space on the surface of the graphene film, whereas if the length exceeds the above range, aggregation of the metal oxide occurs, which reduces zinc ion diffusion ability and charge mobility, thereby degrading electrochemical performance and cycling stability.

[0070] According to one embodiment, the metal oxide may be directly bonded to the surface of the graphene film.

[0071] The metal oxide may be directly synthesized and grown on the surface of the graphene film and may be directly bonded without a separate binder.

[0072] According to one embodiment, the flexible electrode material may be binder-free.

[0073] In other words, since the flexible electrode material according to the present invention does not contain binders or additives, it is possible to prevent side reactions and active substance decomposition caused by binders or additives, and to improve the ion diffusion ability and charge mobility of the electrode.

[0074] According to one embodiment, the electrode may be for a zinc ion battery.

[0075] The zinc-ion battery may be an aqueous zinc-ion battery or an all-solid-state zinc-ion battery.

[0076] According to one embodiment, the electrode may be a cathode for a zinc ion battery.

[0077] According to one embodiment, the flexible electrode material may be used as a waterproof electrode.

[0078] According to one embodiment, the flexible electrode may have an energy density of 390Wh / kg or more at a power density of 90W / kg.

[0079] According to one embodiment, the flexible electrode may have a capacity retention rate of 82% or more after 300 charge / discharge cycles at a current density of 1.0 A / g.

[0080] Another aspect of the invention provides a flexible zinc-ion battery comprising a cathode comprising the flexible electrode material, a zinc metal anode, a separator, and an electrolyte.

[0081] The electrolyte may be in a solution or gel state and may include ZnSO4.

[0082] In other words, the flexible electrode material according to the present invention has characteristics that make it applicable to both zinc ion batteries and all-solid-state zinc ion batteries.

[0083] In particular, it has excellent flexibility and waterproofness, and is characterized by being able to exhibit excellent performance even underwater and when folded.

[0084] Another aspect of the present invention provides a method for manufacturing a flexible electrode material, the method including the steps of: dissolving graphene and polyvinylidene fluoride (PVDF) in a solvent to prepare a mixed solution; casting the mixed solution onto a mesh and heating to form a graphene film; separating the graphene film from the mesh; and floating the graphene film in a metal oxide precursor solution and then stirring the metal oxide precursor solution.

[0085] In the step of preparing the mixed solution, an organic solvent may be used as the solvent. For example, N-methyl-2-pyrrolidone may be used as the solvent.

[0086] According to one embodiment, the dissolution is carried out at a temperature of 50° C. to 100° C. for 30 minutes to 2 hours.

[0087] According to one embodiment, the mixed solution is cast into a mesh by a doctor blade method, and the heating is performed at a temperature of 50°C to 150°C.

[0088] The heating may be performed in an oven at a temperature of 50° C. to 150° C., and a graphene film may be formed by the heat drying.

[0089] According to one embodiment, the method may further include the steps of separating the graphene film from a mesh and then surface activating the separated graphene film.

[0090] The surface activation may be an acid treatment or an etching step using an acid.

[0091] The surface activation may be carried out for 10 to 120 minutes, and preferably for 30 to 90 minutes.

[0092] The surface activation forms oxygen-containing functional groups on the surface of the graphene film, increasing wettability, promoting a reaction between the mixed solution and carbon of the graphene film, and generating some defects on the surface of the graphene film, allowing metal oxide to grow effectively.

[0093] The metal oxide precursor solution refers to a solution containing reactants for producing a target metal oxide.

[0094] According to one embodiment, the metal oxide is manganese oxide, and the metal oxide precursor solution may include potassium permanganate (KMnO4), sulfuric acid (H2SO4), and deionized water (DIW).

[0095] According to one embodiment, the manganese oxide can be synthesized according to the following reaction formula:

[0096] JPEG0007610882000001.jpg7169

[0097] According to one embodiment, the stirring may be carried out for 30 minutes to 90 minutes.

[0098] By adjusting the time for which the stirring is performed, the size and vertical length of the metal oxide to be synthesized can be adjusted.

[0099] Preferably, the stirring can be carried out for 40 to 80 minutes, and more preferably, for 50 to 70 minutes.

[0100] The stirring time is the reaction time during which the metal oxide is synthesized, and the reaction time can be adjusted to form metal oxides of appropriate size and length.

[0101] Yet another aspect of the present invention provides a zinc-ion battery comprising a cathode comprising the flexible electrode material described above or a flexible electrode material produced by the method described above, an anode comprising zinc metal, a separator, and an electrolyte.

[0102] The electrolyte may be in a solution or gel state.

[0103] Another aspect of the present invention provides an energy storage device comprising the zinc ion battery described above.

[0104] The energy storage device may be an all-solid-state device.

[0105] The present invention will now be described in further detail with reference to examples and comparative examples.

[0106] However, the following examples are given for the purpose of illustrating the present invention, and the content of the present invention is not limited to the following examples.

[0107] Example: Manufacturing of flexible electrode material 1) Graphene film production Graphene and polyvinylidene fluoride (PVDF) were dissolved in N-methyl-2-pyrrolidone at 80° C. for 1 hour.

[0108] The mixed solution was cast onto a stainless steel mesh using a doctor blade method, and then dried by heating in an oven at 100°C.

[0109] The formed graphene film was separated from the mesh and then etched with 1 M hydrochloric acid (HCl) for 1 h to activate the surface of the graphene film.

[0110] 2) Manufacturing of flexible electrode materials The surface-activated graphene film (FGF) was washed several times with deionized water and dried. The surface-activated graphene film was floated in a mixed solution of 18 mM potassium permanganate (KMnO4), 1 M sulfuric acid (H2SO4) and deionized water (DIW), and the solution was stirred at 80°C for 30, 60 or 90 minutes to obtain a flexible electrode material in which free-standing manganese dioxide (MnO2) was synthesized on the graphene film.

[0111] The flexible electrode material was then washed with deionized water and dried.

[0112] Hereinafter, the stirring times will be referred to as Example 1 (30 minutes), Example 2 (60 minutes), and Example 3 (90 minutes).

[0113] Experimental example 1. Confirmation of the morphology and structural characteristics of flexible electrode materials The morphology and structural characteristics of the flexible electrode materials prepared according to the examples were analyzed by field emission scanning electron microscopy (FE-SEM), high resolution transmission electron microscopy (HR-TEM), and energy dispersive spectroscopy (EDS).

[0114] In addition, the crystalline phase of manganese dioxide formed on the examples was analyzed by X-ray diffraction analysis (XRD), and the composition was analyzed by thermogravimetric analyzer (TGA) in the temperature range of 100°C to 900°C under ambient atmosphere.

[0115] The chemical bonding state was analyzed by X-ray photoelectron spectroscopy (XPS).

[0116] FIG. 3 is an image showing the morphological and structural characteristics of a flexible electrode material according to one embodiment of the present invention.

[0117] FIG. 3A is a photograph showing the surface-activated graphene film in a bent state.

[0118] 3B and 3F are FE-SEM images of the surface-activated graphene film.

[0119] 3C and 3G are FE-SEM images of the flexible electrode material of Example 1.

[0120] 3D and 3H are FE-SEM images of the flexible electrode material of Example 2.

[0121] 3E and 3I are FE-SEM images of the flexible electrode material of Example 3.

[0122] 3A to 3I, it can be seen that the longer the growth time by stirring, the more MnO2 grows.

[0123] In the case of Example 1, a short growth time (30 min) resulted in the appearance of empty spaces, while in the case of Example 3, a long growth time (90 min) resulted in the aggregation of MnO2.

[0124] In contrast, in the case of Example 2, it can be seen that MnO2 was grown with a uniform distribution on the surface of the graphene film.

[0125] Also, in the case of Example 1, small, vague needle-like particles with a lot of empty space appeared in a relatively wide size distribution (22.3-81.6 nm), while in the case of Example 3, large needle-like MnO2 appeared in a wider size distribution (128.2-137.6 nm) with signs of aggregation.

[0126] In contrast, in Example 2, it can be seen that clear needle-like MnO2 particles are well-dispersed on the surface of the surface-activated graphene without any vacant spaces or aggregation and appear with a relatively uniform size distribution (103.7 to 110.2 nm).

[0127] FIG. 4 is a cross-sectional FE-SEM image of a flexible electrode material of Example 2 according to an embodiment of the present invention.

[0128] FIG. 4A is a cross-sectional FE-SEM image (scale bar 500 nm) of a flexible electrode material of Example 2 according to an embodiment of the present invention.

[0129] FIG. 4B is a cross-sectional FE-SEM image (scale bar 50 nm) of a flexible electrode material of Example 2 according to an embodiment of the present invention, which is an enlarged view of the area indicated by a square in FIG. 4A.

[0130] Referring to FIG. 4, it can be seen that MnO2 is well fixed and dispersed on the surface-activated graphene film.

[0131] FIG. 5 shows HR-TEM images and EDS mapping images of the flexible electrode material of Example 2 according to one embodiment of the present invention.

[0132] FIG. 5A is a low-resolution HR-TEM image of the flexible electrode material of Example 2.

[0133] FIG. 5B is a high-resolution HR-TEM image of the flexible electrode material of Example 2, which is an enlargement of the area indicated by the square in FIG. 5A.

[0134] 5A and 5B, needle-shaped MnO2 particles having a size range of 101.3 to 118.1 nm formed on the flexible electrode material can be seen. Furthermore, it can be seen that it exhibits a lattice distance of 0.69 nm, which coincides with the (110) plane of α-MnO2.

[0135] FIG. 5C is an EDS mapping image of the flexible electrode material of Example 2.

[0136] Referring to FIG. 5C, it can be seen that manganese, oxygen and carbon are uniformly dispersed on the surface of the flexible electrode material.

[0137] FIG. 6 shows the TGA, XRD and XPS results of a flexible electrode material according to one embodiment of the present invention.

[0138] FIG. 6A shows the TGA results of a flexible electrode material according to one embodiment of the present invention.

[0139] Referring to FIG. 6A, it can be seen that the surface-activated graphene film exhibits 100% weight loss, indicating that the graphene film has a pure carbon composition and is free of impurities.

[0140] In comparison, Examples 1 to 3 showed weight losses of 3.2%, 6.5%, and 9.7%, respectively, which means that more MnO2 grew on the surface of the surface-activated graphene film with increasing treatment time.

[0141] FIG. 6B is an XRD result of a flexible electrode material according to one embodiment of the present invention.

[0142] Referring to FIG. 6B, it was confirmed that in both the surface-activated graphene film and Examples 1 to 3, peaks appeared at 26.5° and 54.6°, which correspond to the (002) and (004) layers of graphite, and thus it was confirmed that graphene was stacked to form a layered structure. In Examples 1 to 3, this could not be confirmed since the weight of MnO2 was less than 10% by weight.

[0143] 6C and 6D are XPS results of a flexible electrode material according to one embodiment of the present invention.

[0144] Referring to Figures 6C and 6D, the Mn2p shoulder peaks at 654.5 eV and 642.7 eV can be seen to coincide with the typical spin energy splitting of 11.8 eV for MnO2, and the peaks at 532.6 eV, 531.5 eV, and 530.2 eV in the O1s spectrum correspond to HOH, hydrated trivalent Mn-OH, and tetravalent Mn-O-Mn bonds, respectively.

[0145] This indicates that α-MnO2 was successfully synthesized on the surface of the surface-activated graphene film.

[0146] Experimental Example 2: Evaluation of the electrochemical characteristics of a zinc-ion battery using flexible electrode material A CR2032 type coin cell was manufactured by using the flexible electrode material manufactured in the embodiment as the cathode, zinc metal as the anode, glass fiber paper as the separator, and 2M zinc sulfate (ZnSO4) as the electrolyte.

[0147] The electrochemical behavior of the cell was analyzed by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV).

[0148] Rate characteristic tests are performed at 0.1, 0.3, 0.5, 0.7, 1.0, 1.3, 1.5 and 2.0Ag -1 At a current density of 1.0 to 1.9 V (vs Zn / Zn 2+ ) potential range, and long-term cycling tests were performed at 1.0Ag for up to 300 cycles. -1 The current density was 100 Ω / s.

[0149] FIG. 7 shows the results of analyzing the electrochemical performance of coin cells manufactured using the electrode materials of Examples 1 to 3 and the Comparative Example in which commercial MnO2 powder, PVDF binder, and conductive carbon black are cast onto a surface-activated graphene film.

[0150] FIG. 7A is a Nyquist plot of cells manufactured using the electrode materials of the comparative example and examples 1 to 3. Here, the slope of the semicircle in the high frequency region and the low frequency region indicates the charge transfer resistance (Rct) and ion diffusion behavior (Warburg impedance).

[0151] Referring to FIG. 7A, it can be seen that the semicircle appears smaller in the example than in the comparative example, but this is because there is no binder that can prevent the active substance from approaching.

[0152] Furthermore, Example 2 exhibits the steepest slope, that is, the lowest Warburg impedance, and is therefore found to have the best zinc ion diffusion ability.

[0153] The Warburg impedance coefficient (σw) was calculated using Equation 1, and the Zn ion diffusion coefficient (D) was calculated using Equation 2.

[0154]

number

[0155]

number

[0156] Here, R e indicates the type of total electrode resistance called bulk resistance, D is the Zn ion diffusion coefficient, R is the gas constant, T is the temperature, A is the electrode area, n is the number of electrons per molecule, F is the Faraday constant, and C is the Zn ion molar concentration.

[0157] FIG. 7B shows the results of the measurement of the Z real and ω -1 / 2 1 is a graph showing the relationship between

[0158] Referring to FIG. 7B, the Warburg impedance coefficients (σw) calculated in this manner were 23.6, 23.8, 14.2, and 26.7 Ωcm for the comparative example, Examples 1 to 3, respectively. 2 s -1 / 2 It can be seen that this applies.

[0159] FIG. 7C is a graph showing the Zn ion diffusion coefficients of cells manufactured using the electrode materials of the Comparative Example and Examples 1 to 3.

[0160] The Zn ion diffusion coefficients were 0.61, 0.60, 1.68, and 0.48×10 for the comparative example, Examples 1 to 3, respectively. -12 cm 2 s -1 It was calculated that:

[0161] This shows that the zinc ion diffusion performance is increased in Example 2 in which MnO2 is uniformly dispersed without a binder.

[0162] FIG. 8 is a graph showing the electrochemical performance of cells manufactured using the electrode materials of the comparative example and examples 1 to 3.

[0163] FIG. 8A shows the potentials in the range of 1.0 to 1.9 V and 0.1 to 2.0 Ag of the cells manufactured using the electrode materials of the comparative example and Examples 1 to 3. -1 The rate characteristics are shown in the range of current density.

[0164] Referring to FIG. 8A, Example 2 exhibits a high specific capacity of 0.1Ag -1 From 430.5mAhg -1 It can be seen that the battery exhibits excellent recovering capacity (97.8% capacity retention).

[0165] In comparison, Example 1 exhibited a low discharge capacity, and Example 3 exhibited a rapid loss of discharge capacity and a low capacity retention rate (80.0%).

[0166] FIG. 8B shows the results of the 1.0Ag charge / discharge test of the cells manufactured using the electrode materials of the comparative example and the examples 1 to 3. -1 1 is a graph showing the change in capacity over 300 cycles at a current density of 1000 s.p.m.

[0167] Referring to FIG. 8B, it can be seen that the capacity retention rates of the comparative example and Examples 1 to 3 are 37.2%, 62.8%, 82.7%, and 45.8%, respectively.

[0168] This shows that all of the Examples exhibited improved capacity retention rates compared to the Comparative Examples, and Example 2 secured a capacity retention rate of 82% or more, thereby exhibiting the most excellent long-term stability.

[0169] FIG. 9 compares the energy and power density of cells fabricated using the electrode material of Example 2 with other reported energy storage devices using electrolyte solutions via Ragone plots.

[0170] Referring to FIG. 9, Example 2 is 90Wkg -1 With a power density of 396Whkg -1 It has a maximum energy density of 1,800Wkg and a power density of 201Whkg -1 It can be seen that it shows the maximum energy density.

[0171] In other words, it can be seen that the cell using the electrode material of Example 2 exhibits higher power density and energy density than previously reported supercapacitors, lithium ion batteries, sodium ion batteries, aluminum ion batteries, magnesium ion batteries, and potassium ion batteries.

[0172] Experimental Example 3: Evaluation of the electrochemical characteristics of an all-solid-state zinc-ion battery using flexible electrode materials In addition, an all-solid-state zinc-ion battery was manufactured by using the flexible electrode material manufactured in the examples as the cathode, zinc metal as the anode, glass fiber paper as the separator, and a gel made of a mixture of 1M zinc sulfate (ZnSO4), 1.5M polyvinyl alcohol (PVA) and deionized water (DIW) as the electrolyte.

[0173] The solid-state zinc-ion battery is packaged in a sealing film as an exterior material and is 5 ~10 -2 The electrochemical behavior was investigated via EIS using an AC signal of 5 mV in the Hz frequency range.

[0174] Rate characteristic tests are performed at 0.3, 0.5 and 1.0Ag -1 Long-term cycling tests were performed at a current density of 0.5Ag -1 The samples were subjected to the current density test up to 100 times in both flat and folded states while immersed in water.

[0175] FIG. 10 shows a schematic diagram of an all-solid-state zinc-ion battery structure using flexible electrode materials and gel electrolyte according to one embodiment of the present invention.

[0176] FIG. 11 shows the life performance and cycling stability of an all-solid-state zinc-ion battery using a flexible electrode material and gel electrolyte according to one embodiment of the present invention.

[0177] FIG. 11A shows the potential in the range of 1.0 to 1.9 V and the current density in the range of 0.3 to 1.0 Ag of an all-solid-state zinc-ion battery according to one embodiment of the present invention. -1 The rate characteristics are shown in the range of current densities.

[0178] Referring to FIG. 11A, all-solid-state zinc-ion batteries were tested at 0.3, 0.5 and 1.0 Ag -1 Current densities of 145.6, 100.8 and 45.6mAhg -1 Offering an excellent specific capacitance of 0.3Ag -1 From 131.6mAhg -1 It can be confirmed that the recovery capacity is 90.4%.

[0179] FIG. 11B is a Ragone plot comparing the energy and power density of an all-solid-state zinc-ion battery according to one embodiment of the present invention with previously reported all-solid-state energy storage devices.

[0180] Referring to FIG. 11B, an all-solid-state zinc-ion battery according to an embodiment of the present invention has a power density of 270 Whkg -1 From 131Wkg -1 This is a superior energy density to any previously reported all-solid-state energy storage device.

[0181] FIG. 11C shows the charge-discharge current (Pd) of a 0.5A g all-solid-state zinc-ion battery in a flat and folded state and in the presence and absence of water according to an embodiment of the present invention. -1 The results show cycling stability at a current density of 1000 s.

[0182] Referring to FIG. 11C, it can be seen that the all-solid-state zinc-ion battery according to an embodiment of the present invention has a capacity retention rate of 85% or more during 100 cycles under all conditions, thereby having high flexibility and waterproofness.

[0183] FIG. 12 is a photograph showing an experiment to confirm the operation of the all-solid-state zinc ion battery according to an embodiment of the present invention in water and in a bent state.

[0184] Referring to FIG. 12, an all-solid-state zinc-ion battery according to an embodiment of the present invention can be seen illuminating a light-emitting diode (LED) underwater and powering a drone propeller when bent.

[0185] As a result, it can be seen that the all-solid-state zinc ion battery according to an embodiment of the present invention can be practically used as an energy storage device having excellent electrochemical performance, flexibility, and waterproofness.

[0186] As described above, although the embodiments have been described with reference to limited drawings, those skilled in the art can apply various technical modifications and variations based on the above. For example, the techniques described may be performed in different orders than described, and / or components of the described systems, structures, devices, circuits, etc. may be combined or combined in different ways than described, or substituted or substituted by other components or equivalents, and still achieve suitable results.

[0187] Therefore, other embodiments, examples, and equivalents to the claims are also within the scope of the following claims.

Claims

1. A flexible electrode material for a cathode of a zinc-ion battery, comprising a graphene film and a needle-shaped free-standing metal oxide formed on the graphene film, The flexible electrode material, wherein the metal oxide is α-MnO 2 .

2. The flexible electrode material of claim 1 , wherein the graphene film comprises graphene or a plurality of graphene stacks.

3. The flexible electrode material of claim 1 , wherein the graphene film is surface-activated and has oxygen (O)-containing functional groups on the surface.

4. The flexible electrode material as described in claim 1, wherein the content of the metal oxide is 1% by weight to 10% by weight.

5. The flexible electrode material according to claim 1 , wherein the length of the metal oxide in a direction perpendicular to the surface of the graphene film is 10 nm to 200 nm.

6. 10. The flexible electrode material of claim 1, wherein the metal oxide is directly bonded to a surface of the graphene film.

7. 7. The flexible electrode material according to claim 6, which is binder-free.

8. 2. The flexible electrode material according to claim 1, wherein the electrode is for a zinc ion battery.

9. 1. A method for manufacturing a flexible electrode material for a cathode of a zinc-ion battery, comprising: dissolving graphene and polyvinylidene fluoride in a solvent to prepare a mixed solution; casting the mixed solution into a mesh and heating to form a graphene film; separating the graphene film from the mesh; and floating the graphene film in a metal oxide precursor solution and then stirring the metal oxide precursor solution to form a free-standing metal oxide on the graphene film.

10. The mixed solution is cast into a mesh by doctor blade method, The method for manufacturing a flexible electrode material according to claim 9, wherein the heating is performed at a temperature of 50°C to 150°C.

11. The metal oxide is manganese oxide, The method for manufacturing a flexible electrode material according to claim 9, wherein the metal oxide precursor solution comprises potassium permanganate, sulfuric acid and deionized water.

Citation Information

Patent Citations

  • Preparation method of graphene and manganous manganic oxide composite electrode material

    CN104319108A

  • Zinc ion secondary battery and method for manufacturing the same

    JP2016520969A

  • Zinc secondary battery electrode active material and secondary battery including the same

    JP2020047572A

  • Self assembled multi-layer nanocomposite of graphene and metal oxide materials

    US20110033746A1